Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/clen.201200448
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Landscape Connectivity in a Urban Area for Biological Conservation

Abstract: Biodiversity conservation in urbanized area is an increasing challenge worldwide. A quantitative tool is needed to provide a spatially explicit representation of habitat mosaics and thus afford insight into the ecological consequences of landscape changes. We developed a method for identifying core habitats and generating a cost surface that was used to identify both the permeability of the landscape matrix and the quality of core habitats and then we developed a least-cost model to delimit the links between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(50 reference statements)
0
4
0
1
Order By: Relevance
“…Previous studies in urban areas have estimated connectivity for birds within and between public green spaces1617181920. These studies suggest that vegetation between green spaces preserves connectivity, while multiple barriers, such as roads and rivers, cumulatively decrease landscape permeability.…”
mentioning
confidence: 99%
“…Previous studies in urban areas have estimated connectivity for birds within and between public green spaces1617181920. These studies suggest that vegetation between green spaces preserves connectivity, while multiple barriers, such as roads and rivers, cumulatively decrease landscape permeability.…”
mentioning
confidence: 99%
“…Studies of structural connectivity in urban settings have highlighted its importance and utility as an aid to planning (e.g. Marulli and Mallarach 2005;Yu et al 2015); however, the unique complexity and high heterogeneity of these environments renders them particularly difficult to study in this regard, and numerous gaps remain in our understanding of how urban form influences ecological function (LaPoint et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The application of modelling techniques and connectivity indexes allow us detecting how meandering is influenced by other dynamic fluxes such as agricultural fields [91] or urban areas [92] and at which level. Therefore, undoubtedly, understanding connectivity processes in the Sajó river would help land plan managers and stakeholders to design correct and sustainable soil erosion control measures and water conservation practices, as other authors also confirmed in other degraded areas [93,94].…”
Section: Discussionmentioning
confidence: 66%